Refusing to tolerate ongoing prejudicial behavior toward immigrants: Together we can object to prejudicial flag displays - Gausel, Nicolay; Berndsen, Mariëtte (Frontiers in Psychology, 2022)
Over recent years, immigrants have been met with unjust prejudiced behaviour instead of warm welcome. However, not all citizens of a nation endorse such behaviour, instead they try to oppose it through social mobilisation. In the context of an ongoing situation where the national flag is used as a prejudiced means to exclude immigrants, individuals who felt attached with all members of the nation felt significantly more shame for the unjust than individuals who glorify their nation. Consequently, attached identifiers expressed a significantly greater motivation than glorified identifiers to start thinking about social mobilisation to reclaim the meaning of the flag as a symbol of inclusion, not exclusion. The current study contributes to the growing debate on how immigrants are received, and it helps explain how national identification and feelings such as shame motivate individuals to start thinking about objecting to prejudicial flag displays.